Investment Commitments in East Asia and Pacific Remained Stable in 2007 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in East Asia and Pacific grew by 11 percent to US$21.5 billion in 2007, according to just-released data from the private participation in infrastructure project database. The region accounted for 13.6 percent of the year's total investment commitments in developing countries. Investment commitments in the region, while they have recovered from the low level of US$12.3 billion in 2002, remained in the US$19-21 billion range for the third consecutive year. The 2007 level is just 46 percent of the peak in 1997. Investment in 2007 was driven by both new projects and projects implemented in previous years. The 104 new projects accounted for US$11.7 billion, while projects reaching financial closure in 1990-2006 attracted US$9.8 billion. Investment in physical assets amounted to US$17 billion, returning to a level similar to those in 2003 and 2005. Payments to the government amounted to US$4.5 billion.